Carcinosarcoma with chondroid differentiation and neuroendocrine carcinoma: unusual triphasic tumour arising from intracholecystic papillary neoplasm of the gall bladder. Issue 7 (20th July 2022) - Mruthyunjayappa, Smitha; Patel, Chirag Rasiklal; Reddy, Sushanth; Al Diffalha, Sameer
Abstract : Herein, we report a man in his 70s with gallbladder mass. Microscopically, the tumour demonstrated moderately differentiated adenocarcinoma, sarcoma with focal chondroid differentiation and high-grade neuroendocrine tumour component arising in an intracholecystic papillary neoplasm. The patient did not receive adjuvant chemotherapy in the setting of complete surgical resection. Patient presented with extensive metastasis after 47 months and died 3 months later. Due to the low incidence and poor prognosis of this tumour, it is essential to gather all the individual experience-based information. To our knowledge, this is the first reported case of carcinosarcoma arising from intracholecystic papillary–tubular neoplasm.